Doživljanje neizvedene zdravstvene nege pri medicinskih sestrah - Bahun, Mateja (Obzornik zdravstvene nege, 2023)
Introduction:Stress related to nursing care that is missed for a variety of reasons is often overlooked and unrecognized. The purpose of integrative literature review is to review the latest research that examines how missed nursing care is reflected in nurses' mental well-being.Methods: We used integrative literature review conducted according to PRISMA guidelines in the databases PubMed, CINAHL, Wiley, COBISS.SI and Google Scholar. The process of searching and analyzing the literature is shown using a PRISMA diagram. The results were sorted according to the level of evidence. A thematic content analysis was used.Results: A total of 175 sources were identified and 11 were included in the final analysis. 96 codes were identified and grouped into 4 categories: (1) Physical, mental and emotional well-being, (2) Moral and ethical dilemmas, (3) Decision making at work - adaptation, (4) Professional and personal values.Discussion and conclusion: Missed nursing care is an important source of distress and stress for nurses as due to not being able to perform all the necessary activities in nursing, they come into conflict with their personal and professional values. Our results add a substantive context and a better understanding of the consequences of missed nursing care in nurses. Daily decision-making of which activities will be omitted affects not only the nurses' well-being, dissatisfaction and burn-out, but also contribute to the decision to leave their job position or profession.
Keywords: duševno počutje; emotional well-being; missed; neopravljena; omitted; opuščena; psihično počutje; psychological well-being; racionalizacija; rationalisation; stres; stress